The Literacy Crisis of Elementary School Students in Indonesia: A Systematic Literature Review - Sabilah, Ceriagu Anisa Ray; Utama, Candra (Proceedings Series of Educational Studies, 2024)
Motivated by the current low literacy of elementary school students, this research aims to analyze the literacy crisis in elementary school students in Indonesia through the systematic literature review (SLR) method by collecting data from previous research results within the last eight years related to low literacy, elementary school literacy, and literacy crisis. The search for research articles uses publish or perish application with the google scholar database and is carried out with three SLR stages starting from planning, implementation, and reporting. The results of this study show that low literacy can be a literacy crisis in the younger generation. Therefore, the solution offered to overcome the literacy crisis in elementary schools starts with the Gerakan Literasi Sekolah (GLS).